2014
DOI: 10.1177/0193945913520414
|View full text |Cite
|
Sign up to set email alerts
|

Features of Online Health Communities for Adolescents With Type 1 Diabetes

Abstract: The aim of this exploratory study was to examine diabetes online health communities (OHCs) available to adolescents with type 1 diabetes (T1D). We sought to identify and classify site features and relate them to evidence-based processes for improving self-management. We reviewed 18 OHCs and identified the following five feature categories: social learning and networking, information, guidance, engagement, and personal health data sharing. While features that have been associated with improved self-management w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(49 citation statements)
references
References 44 publications
2
46
0
1
Order By: Relevance
“…Social media can serve as an aid to patients. For example, it fosters their autonomy by complementing the information provided by healthcare professionals [1] and by providing psychosocial support [2]. Social media use by patients can also be an aid to healthcare professionals by providing a tool to strengthen the organization’s market position [3, 4] and stimulating conversation for brand building and improved service delivery [4, 5].…”
Section: Introductionmentioning
confidence: 99%
“…Social media can serve as an aid to patients. For example, it fosters their autonomy by complementing the information provided by healthcare professionals [1] and by providing psychosocial support [2]. Social media use by patients can also be an aid to healthcare professionals by providing a tool to strengthen the organization’s market position [3, 4] and stimulating conversation for brand building and improved service delivery [4, 5].…”
Section: Introductionmentioning
confidence: 99%
“…As suggested by findings regarding utility of social media, web‐based resources appeared to be a useful strategy for engaging individuals with T1DM and for providing emotional support and information exchange . Social media use (Facebook and Skype) and online health communities allowed adolescents with T1DM and their parents to gain and share diabetes knowledge and information, to cope better with their daily life, to improve self‐management, and to achieve diabetes control . In addition, as shown by previous research, chat line participation was found to be a useful tool for adolescents to improve coping with T1DM and gaining metabolic control (Hb1Ac values) and quality of life as well …”
Section: Introductionmentioning
confidence: 66%
“…Among the selected studies, there is an association between rewards and improved frequency of glycemic monitoring, since this resource increases the intrinsic motivation for self-care and adolescents' competence to reach their goals. (2,12,15) Based on adolescents' resistance to approach healthcare professionals, a study sought to promote interaction through messages sent by an application. (7) Another study added an in-app feature for users' communication with their peers in a chat room to share experiences and obtain or provide support.…”
Section: Discussionmentioning
confidence: 99%
“…(1) Inadequate control has been linked to short-term consequences such as hypoglycemia, hyperglycemia and diabetic ketoacidosis, and to long-term consequences such as limb amputation, retinopathy and renal failure. (2) One of the educational strategies to prevent complications of this chronic condition is using mobile applications that allow human-machine interaction through a set of interface characteristics by providing interactive experiences and facilitating data collection. (3,4) This communication technology has emerged as a new application model for self-care in which individuals take control of their health through information.…”
Section: Introductionmentioning
confidence: 99%